Positive electrode sheet, battery cell, battery and power-using device
By layering the active materials with different liquid absorption rates in the positive electrode sheet, the problems of long wetting time and uneven current are solved, and a higher capacity retention rate and energy density are achieved.
Patent Information
- Application Number
- CN202311405495.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-27
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-10-27
AI Technical Summary
In the positive electrode sheet, the difference in liquid absorption capacity of different active materials leads to uneven current phenomena and the problem of excessive infiltration time.
By placing the first positive electrode active material with a larger liquid absorption rate on the inner layer, the second positive electrode active material with a smaller liquid absorption rate on the outer layer, and in some embodiments, a third or fourth positive electrode active material is introduced. To optimize the difference in liquid absorption rate, ensure uniform wetting of the entire cathode sheet.
It effectively shortens the wetting time of the positive electrode sheet, reduces the possibility of uneven current phenomenon, improves capacity retention, and has high safety performance and energy density.
Smart Images

Figure CN117133860B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a positive electrode sheet, a battery cell, a battery and an electrical device. Background Art
[0002] In a positive electrode sheet using multiple positive electrode active materials, in order to reduce the possibility of current unevenness between the positive electrode active materials, the positive electrode active materials are usually arranged in layers. Usually, different positive electrode active materials have different abilities to absorb electrolyte, resulting in large differences in the wetting time of each layer, and at the same time, resulting in a longer wetting time for the entire positive electrode sheet. Summary of the invention
[0003] In view of the above problems, the present application provides a positive electrode sheet, a battery cell, a battery and an electrical device, which can improve the problem of long wetting time of the positive electrode sheet.
[0004] In a first aspect, the present application provides a positive electrode sheet, comprising a positive electrode collector and a positive electrode active material layer, the positive electrode active material layer being disposed on at least one surface of the positive electrode collector, the positive electrode active material layer comprising a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer being disposed between the second positive electrode active material layer and the positive electrode collector, the first positive electrode active material layer comprising a first positive electrode active material, the second positive electrode active material layer comprising a second positive electrode active material, and the liquid absorption rate of the first positive electrode active material being greater than the liquid absorption rate of the second positive electrode active material.
[0005] In the technical solution of the embodiment of the present application, the first positive electrode active material with a larger liquid absorption rate is placed in the inner layer, and the second positive electrode active material with a smaller liquid absorption rate is placed in the outer layer. When used as a battery, the second positive electrode active material in the outer layer has a larger contact area with the electrolyte and is closer to the electrolyte, which can shorten the infiltration time of the second positive electrode active material with a smaller liquid absorption rate; and the first positive electrode active material in the inner layer has a larger liquid absorption rate, which can make up for its shortcoming of being far away from the electrolyte and can still be infiltrated in a shorter time, thereby improving the infiltration time of the entire positive electrode sheet. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle.
[0006] In some embodiments, the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: ab≧1 μg / s.
[0007] In the above implementation process, by controlling the difference between the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material to exceed 1 μg / s, the first positive electrode active material with a larger liquid absorption rate in the inner layer can help the second positive electrode active material with a smaller liquid absorption rate in the outer layer to achieve infiltration from the inside after being fully infiltrated, thereby further shortening the infiltration time of the entire positive electrode sheet.
[0008] In some embodiments, the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: 2 μg / s≤ab≤4 μg / s.
[0009] In the above implementation process, the difference between the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material is in the range of 2-4 μg / s, which can further increase the effect of the first positive electrode active material with a larger liquid absorption rate in the inner layer helping the second positive electrode active material with a smaller liquid absorption rate in the outer layer to achieve wetting from the inside. At the same time, it can reduce the possibility that the first positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate failing to achieve good wetting.
[0010] In some embodiments, the second positive electrode active material layer includes a first region and a second region, the first region includes the second positive electrode active material, the second region includes the third positive electrode active material, and the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: c>b.
[0011] In the above implementation process, by using the third positive electrode active material with a larger liquid absorption rate and the second positive electrode active material with a smaller liquid absorption rate to form the second positive electrode active material layer, the third positive electrode active material with a larger liquid absorption rate can accelerate the infiltration of the second positive electrode active material layer. At the same time, to a certain extent, it can also help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration, further accelerating the infiltration of the second positive electrode active material layer.
[0012] In some embodiments, the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: cb ≥ 1 μg / s;
[0013] Optionally, the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5 μg / s≤cb≤5 μg / s.
[0014] In the above implementation process, by controlling the difference between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not less than 1 μg / s, the third positive electrode active material with a larger liquid absorption rate can better help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration. At the same time, controlling the difference between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not more than 5 μg / s can reduce the possibility that the third positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate failing to achieve good infiltration.
[0015] In some embodiments, the second region is located in a central region of the second positive electrode active material layer.
[0016] In the above implementation process, the third positive electrode active material with a higher liquid absorption rate is arranged in the central area of the second positive electrode active material layer which is relatively difficult to be wetted. Its higher liquid absorption rate can make up for the difficulty of wetting the central area, so that the entire second positive electrode active material layer can be wetted as a whole in a relatively synchronous manner. At the same time, the regional arrangement can reduce the mutual influence between the third positive electrode active material and the second positive electrode active material, which is beneficial to the battery performance.
[0017] In some embodiments, the positive electrode active material layer also includes a third positive electrode active material layer, and the third positive electrode active material layer is arranged on the surface of the second positive electrode active material layer away from the first positive electrode active material layer. The third positive electrode active material layer includes a fourth positive electrode active material, and the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: d>b.
[0018] In the above implementation process, by arranging a third positive electrode active material layer outside the second positive electrode active material layer containing the second positive electrode active material with a lower liquid absorption rate, the third positive electrode active material layer contains a fourth positive electrode active material with a larger liquid absorption rate. After the third positive electrode active material layer and the first positive electrode active material layer are fully infiltrated, they can simultaneously help the second positive electrode active material layer to be infiltrated from both sides of the second positive electrode active material layer, thereby shortening the infiltration time of the entire positive electrode sheet.
[0019] In some embodiments, the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: db ≥ 1 μg / s;
[0020] Optionally, the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5 μg / s≤db≤5 μg / s.
[0021] In the above implementation process, by controlling the difference between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not less than 1 μg / s, the fourth positive electrode active material with a larger liquid absorption rate can better help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration. At the same time, controlling the difference between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not more than 5 μg / s can reduce the possibility that the fourth positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate being unable to achieve good infiltration.
[0022] In some embodiments, the ultimate compaction density of the first positive electrode active material is 3.4-3.75 g / cm 3 ; and / or
[0023] The ultimate compaction density of the second positive electrode active material is 2.1-2.4 g / cm 3 ; and / or
[0024] The ultimate compaction density of the third positive electrode active material is 3.4~3.75 g / cm 3 ; and / or
[0025] The ultimate compaction density of the fourth positive electrode active material is 3.4-3.75 g / cm 3 .
[0026] In the above implementation process, the ultimate compaction density of the positive electrode active material is usually positively correlated with its liquid absorption rate. The greater the ultimate compaction density, the greater the liquid absorption rate. The ultimate compaction density is 2.1~2.4g / cm 3 The second positive electrode active material can have a limiting compaction density of 3.4~3.75g / cm 3 The first positive electrode active material with a maximum compaction density of 3.4-3.75 g / cm 3 The third positive electrode active material and the ultimate compaction density are 3.4~3.75g / cm 3 A good liquid absorption rate difference is formed between the fourth positive electrode active materials, thereby shortening the wetting time of the entire electrode.
[0027] In some embodiments, the ultimate compaction density of the first positive electrode active material is 3.55-3.7 g / cm 3 ; and / or
[0028] The ultimate compaction density of the second positive electrode active material is 2.25-2.4 g / cm 3 ; and / or
[0029] The ultimate compaction density of the third positive electrode active material is 3.55~3.7g / cm 3 ; and / or
[0030] The ultimate compaction density of the fourth positive electrode active material is 3.55~3.7g / cm 3 .
[0031] In some embodiments, the first cathode active material comprises a ternary system material; and / or
[0032] The second positive electrode active material comprises a polyanion positive electrode material; and / or
[0033] The third positive electrode active material includes a ternary system material; and / or
[0034] The fourth positive electrode active material includes a ternary system material.
[0035] In the above implementation process, polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet have both higher safety performance and higher energy density.
[0036] In some embodiments, the polyanion positive electrode material includes at least one of lithium iron phosphate, lithium manganese phosphate and LiMPO4, M in LiMPO4 includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.
[0037] Optionally, the first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.
[0038] Optionally, the second doping element includes one or more elements of B, S, Si and N.
[0039] Optionally, the polyanion cathode material includes Li 1+x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
[0040] Optionally, the polyanion cathode material includes Lih A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
[0041] In some embodiments, the polyanionic cathode material further has a coating layer comprising carbon.
[0042] In the above implementation process, the introduction of the carbon-containing coating layer is used to improve the liquid absorption rate and conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually a core-shell structure with LiMPO4 as the core and the surface of the core covered with the coating layer.
[0043] In some embodiments, the carbon-containing coating layer accounts for 1% to 3% by mass in the polyanion positive electrode material;
[0044] Optionally, the carbon-containing coating layer accounts for 1.5% to 2.5% by mass in the polyanion positive electrode material.
[0045] In the above implementation process, by controlling the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material to 1% to 3%, the second positive electrode active material has a better liquid absorption rate. At the same time, the energy density of the electrode can also be taken into account.
[0046] In some embodiments, the ternary system material includes nickel-cobalt-manganese ternary material and modified materials thereof and nickel-cobalt-aluminum ternary material and modified materials thereof.
[0047] In the above implementation process, the modified material of the nickel-cobalt-manganese ternary material and the modified material of the nickel-cobalt-aluminum ternary material refer to materials obtained by doping or coating the nickel-cobalt-manganese ternary material or the nickel-cobalt-aluminum ternary material, respectively.
[0048] In some embodiments, the ternary system material includes Li a Ni b Co c M1 d M2 e Of R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 includes one or two elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
[0049] In a second aspect, the present application provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector is disposed on at least one surface of the positive electrode active material layer. The positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer. The first positive electrode active material layer is disposed between the second positive electrode active material layer and the positive electrode current collector. The first positive electrode active material layer includes a first positive electrode active material, and the first positive electrode active material includes a ternary system material; the second positive electrode active material layer includes a second positive electrode active material, and the second positive electrode active material includes a polyanion positive electrode material; the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: a - b ≥ 1 μg / s.
[0050] In the technical solution of the embodiment of the present application, the first positive electrode active material with a larger liquid absorption rate is placed in the inner layer, and the second positive electrode active material with a smaller liquid absorption rate is placed in the outer layer. When used as a battery, the contact area between the second positive electrode active material in the outer layer and the electrolyte is larger and the distance is closer, which can shorten the wetting time of the second positive electrode active material with a smaller liquid absorption rate; while the first positive electrode active material in the inner layer has a larger liquid absorption rate, which can make up for the disadvantage of its longer distance from the electrolyte and still can achieve wetting in a shorter time; thus improving the wetting time of the entire positive electrode sheet. At the same time, by controlling the difference in the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material to exceed 1 μg / s, after the first positive electrode active material with a larger liquid absorption rate in the inner layer is fully wetted, it can also help the second positive electrode active material with a smaller liquid absorption rate in the outer layer to achieve wetting from the inside, further reducing the wetting time of the entire positive electrode sheet. And by disposing the first positive electrode active material and the second positive electrode active material in layers, the possibility of uneven current between the first positive electrode active material and the second positive electrode active material can be reduced, thereby enabling the positive electrode sheet to have a higher capacity retention rate in the early stage of cycling. In addition, polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit high energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can enable the positive electrode sheet to have both high safety performance and high energy density.
[0051] In a third aspect, the present application provides a battery cell, the battery cell comprising the positive electrode sheet provided in the first aspect or the second aspect.
[0052] In a fourth aspect, the present application provides a battery, the battery comprising the battery cell provided in the third aspect.
[0053] In a fifth aspect, the present application provides an electrical device, which includes the battery cell provided in the third aspect or the battery provided in the fourth aspect. BRIEF DESCRIPTION OF THE DRAWINGS
[0054] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present application. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0055] Figure 1 A schematic diagram of the structure of a vehicle provided in some embodiments of the present application;
[0056] Figure 2 A schematic diagram of the exploded structure of a secondary battery provided in some embodiments of the present application;
[0057] Figure 3 A schematic diagram of the structure of a battery cell provided in some embodiments of the present application;
[0058] Figure 4 An exploded view of a battery cell provided for some embodiments of the present application;
[0059] Figure 5 A first structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;
[0060] Figure 6 A second structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;
[0061] Figure 7 A schematic diagram of the structure of a second positive electrode active material layer provided in some embodiments of the present application;
[0062] Figure 8 A third structural schematic diagram of a positive electrode sheet provided in some embodiments of the present application;
[0063] Fig. 9 A flow chart of a method for preparing a positive electrode sheet provided in some embodiments of the present application.
[0064] The reference numerals in the specific implementation manner are as follows:
[0065] 1000-vehicle; 100-secondary battery; 200-motor; 300-controller; 10-housing; 11-accommodating space; 12-first part; 13-second part; 20-battery cell; 21-housing; 211-opening; 22-end cover assembly; 221-end cover; 222-electrode terminal; 23-electrode assembly; 231-positive electrode sheet; 2311-positive current collector; 2312-positive active material layer; 2312a-first positive active material layer; 2312b-second positive active material layer; C-central area; 2312c-third positive active material layer; 24-current collecting member; 25-insulating protection member. DETAILED DESCRIPTION
[0066] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.
[0067] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.
[0068] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0069] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0070] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0071] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).
[0072] In the description of the embodiments of the present application, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, which are only for the convenience of describing the embodiments of the present application and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as a limitation on the embodiments of the present application.
[0073] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.
[0074] At present, from the perspective of market development, the application of power batteries is becoming more and more extensive. Power batteries are not only used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, but also widely used in electric vehicles such as electric bicycles, electric motorcycles, electric cars, as well as military equipment and aerospace and other fields. With the continuous expansion of the application field of power batteries, the market demand is also constantly expanding.
[0075] The power battery can be a lithium-ion battery, which is widely used in portable electronic devices, electric vehicles and other fields. In the production process of lithium-ion secondary battery electrode plates, a single-layer coating is usually used to coat the required active material on the positive electrode collector. With the increase in energy density and safety performance requirements, some people have proposed the use of positive electrode active materials with high energy density characteristics such as ternary system materials and positive electrode active materials with high safety performance characteristics such as polyanion positive electrode materials to balance energy density and safety performance.
[0076] However, when a positive electrode active material with high energy density characteristics and a positive electrode active material with high safety performance characteristics are directly incorporated into a positive electrode active material layer, current unevenness is likely to occur between the two positive electrode active materials in the positive electrode active material layer. This phenomenon will cause the positive electrode sheet to experience rapid capacity decay in the early stage of the cycle, which will have a significant impact on the capacity retention rate of the positive electrode sheet.
[0077] In order to further improve the problem of rapid attenuation of the electrode in the early stage of the cycle, the active materials can be arranged in layers. However, different positive electrode active materials usually have different absorption capacities for the electrolyte, resulting in large differences in the wetting time of each layer. At the same time, the wetting time of the entire positive electrode sheet is longer.
[0078] Based on the above considerations, in order to shorten the infiltration time of the electrode sheet, the present application proposes a positive electrode sheet, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, the positive electrode active material layer is arranged on at least one surface of the positive electrode current collector, the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, the first positive electrode active material layer is arranged between the second positive electrode active material layer and the positive electrode current collector, the first positive electrode active material layer includes a first positive electrode active material, the second positive electrode active material layer includes a second positive electrode active material, and the liquid absorption rate of the first positive electrode active material is greater than the liquid absorption rate of the second positive electrode active material.
[0079] In such a positive electrode sheet, the first positive electrode active material with a higher liquid absorption rate is placed in the inner layer, and the second positive electrode active material with a lower liquid absorption rate is placed in the outer layer. When used as a battery, the second positive electrode active material in the outer layer has a larger contact area with the electrolyte and is closer to the electrolyte, which can shorten the wetting time of the second positive electrode active material with a lower liquid absorption rate; while the first positive electrode active material in the inner layer has a higher liquid absorption rate, which can make up for its short distance from the electrolyte and still achieve wetting in a shorter time, thereby improving the wetting time of the entire positive electrode sheet. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet have a higher capacity retention rate in the early stage of the cycle.
[0080] The positive electrode sheet can be used to prepare an electrode assembly, which can be used in, but not limited to, electrical devices such as vehicles, ships or aircraft. A power supply system comprising the battery monomers and secondary batteries disclosed in the present application can be used to form the electrical device.
[0081] The embodiment of the present application provides an electric device using a battery as a power source, and the electric device may be, but is not limited to, a mobile phone, a tablet, a laptop, an electric toy, an electric tool, a battery car, an electric car, a ship, a spacecraft, etc. Among them, the electric toy may include a fixed or mobile electric toy, such as a game console, an electric car toy, an electric ship toy, and an electric airplane toy, etc., and the spacecraft may include an airplane, a rocket, a space shuttle, and a spacecraft, etc.
[0082] For the convenience of description, the following embodiments are described by taking a vehicle 1000 as an example of an electrical device according to an embodiment of the present application.
[0083] Please refer to Figure 1 , Figure 1 A schematic diagram of the structure of a vehicle 1000 provided for some embodiments of the present application. The vehicle 1000 may be a fuel vehicle, a gas vehicle or a new energy vehicle, and the new energy vehicle may be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. A secondary battery 100 is provided inside the vehicle 1000, and the secondary battery 100 may be provided at the bottom, head or tail of the vehicle 1000. The secondary battery 100 may be used to power the vehicle 1000, for example, the secondary battery 100 may be used as an operating power source for the vehicle 1000. The vehicle 1000 may also include a controller 300 and a motor 200, and the controller 300 is used to control the secondary battery 100 to power the motor 200, for example, for starting, navigating and driving the vehicle 1000.
[0084] In some embodiments of the present application, the secondary battery 100 can be used not only as an operating power source for the vehicle 1000 , but also as a driving power source for the vehicle 1000 , replacing or partially replacing fuel or natural gas to provide driving power for the vehicle 1000 .
[0085] In the present application, the secondary battery 100 refers to a single physical module including multiple battery cells 20 to provide higher voltage and capacity, which can be in the form of a battery pack, a battery module, etc. The secondary battery 100 can include a box 10 for encapsulating multiple battery cells 20, and the box 10 can prevent liquid or other foreign matter from affecting the charging or discharging of the battery cells 20.
[0086] Figure 2 This is a schematic diagram of the exploded structure of a secondary battery 100 provided in some embodiments of the present application. Figure 2 The secondary battery 100 includes a housing 10 and a battery cell 20 , and the battery cell 20 is accommodated in the housing 10 .
[0087] The box body 10 is used to provide a storage space 11 for the battery cell 20. In some embodiments, the box body 10 may include a first portion 12 and a second portion 13, and the first portion 12 and the second portion 13 cover each other to define the storage space 11 for accommodating the battery cell 20. Of course, the connection between the first portion 12 and the second portion 13 can be sealed by a sealing member (not shown in the figure), and the sealing member can be a sealing ring, a sealant, etc.
[0088] The first part 12 and the second part 13 can be in various shapes, such as a cuboid, a cylinder, etc. The first part 12 can be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20, and the second part 13 can also be a hollow structure with one side open to form a receiving cavity for receiving the battery cell 20. The opening side of the second part 13 covers the opening side of the first part 12, thereby forming a box body 10 with a receiving space 11. Of course, if Figure 2 As shown, the first part 12 may be a hollow structure with one side open, and the second part 13 may be a plate-like structure. The second part 13 covers the open side of the first part 12 to form a box body 10 with an accommodating space 11.
[0089] In the secondary battery 100, there are multiple battery cells 20, and the multiple battery cells 20 can be connected in series, in parallel, or in mixed connection. Mixed connection means that the multiple battery cells 20 are both connected in series and in parallel. The multiple battery cells 20 can be directly connected in series, in parallel, or in mixed connection, and then the whole body formed by the multiple battery cells 20 is accommodated in the box 10; of course, multiple battery cells 20 can also be connected in series, in parallel, or in mixed connection to form a battery module, and then the multiple battery modules are connected in series, in parallel, or in mixed connection to form a whole body, and accommodated in the box 10. The battery cell 20 can be cylindrical, flat, rectangular, or other shapes. Figure 2 The example shows that the battery cell 20 is in a square shape.
[0090] In some embodiments, the secondary battery 100 may further include a busbar component (not shown), and the multiple battery cells 20 may be electrically connected via the busbar component to achieve series connection, parallel connection, or mixed connection of the multiple battery cells 20 .
[0091] Figure 3 This is a schematic diagram of the structure of a battery cell 20 provided in some embodiments of the present application. Figure 4 This is an exploded view of a battery cell 20 provided in some embodiments of the present application. Figure 3 and Figure 4 The battery cell 20 may include a housing 21 , an end cap assembly 22 and an electrode assembly 23 . The housing 21 has an opening 211 , the electrode assembly 23 is accommodated in the housing 21 , and the end cap assembly 22 is used to cover the opening 211 .
[0092] The shape of the housing 21 can be determined according to the specific shape of the electrode assembly 23. For example, if the electrode assembly 23 is a rectangular parallelepiped structure, the housing 21 can be a rectangular parallelepiped structure. Figure 3 and Figure 4 The case where the housing 21 and the electrode assembly 23 are square is exemplarily shown.
[0093] The shell 21 may also be made of a variety of materials, such as copper, iron, aluminum, stainless steel, aluminum alloy, etc., and the embodiment of the present application does not impose any special restrictions on this.
[0094] The end cap assembly 22 includes an end cap 221 and an electrode terminal 222. The end cap assembly 22 is used to seal the opening 211 of the housing 21 to form a closed installation space (not shown), and the installation space is used to accommodate the electrode assembly 23. The installation space is also used to accommodate an electrolyte, such as an electrolyte. The end cap assembly 22 is a component for outputting the electrical energy of the electrode assembly 23. The electrode terminal 222 in the end cap assembly 22 is used to be electrically connected to the electrode assembly 23, that is, the electrode terminal 222 is electrically connected to the tab of the electrode assembly 23. For example, the electrode terminal 222 is connected to the tab through the current collecting member 24 to achieve electrical connection between the electrode terminal 222 and the tab.
[0095] It should be noted that the opening 211 of the shell 21 can be one or two. If the opening 211 of the shell 21 is one, the end cap assembly 22 can also be one, and two electrode terminals 222 can be provided in the end cap assembly 22, and the two electrode terminals 222 are respectively used to electrically connect to the positive pole ear and the negative pole ear of the electrode assembly 23. If the opening 211 of the shell 21 is two, for example, the two openings 211 are provided on opposite sides of the shell 21, and the end cap assembly 22 can also be two, and the two end cap assemblies 22 are respectively covered at the two openings 211 of the shell 21. In this case, the electrode terminal 222 in one end cap assembly 22 can be a positive electrode terminal, which is used to electrically connect to the positive pole ear of the electrode assembly 23; the electrode terminal 222 in the other end cap assembly 22 can be a negative electrode terminal, which is used to electrically connect to the negative electrode sheet of the electrode assembly 23.
[0096] In some embodiments, Figure 4 As shown, the battery cell 20 may further include an insulating protective member 25 fixed to the periphery of the electrode assembly 23, and the insulating protective member 25 is used to insulate and isolate the electrode assembly 23 from the housing 21. Exemplarily, the insulating protective member 25 is a tape bonded to the periphery of the electrode assembly 23. In some embodiments, there are multiple electrode assemblies 23, and the insulating protective member 25 is arranged around the periphery of the multiple electrode assemblies 23, and the multiple electrode assemblies 23 are formed into an integral structure to keep the electrode assembly 23 structurally stable.
[0097] The electrode assembly 23 includes a positive electrode sheet 231, a negative electrode sheet and a separator. The positive electrode sheet 231 includes a positive electrode collector 2311 and a positive electrode active material layer 2312. The positive electrode active material layer 2312 is coated on the surface of the positive electrode collector 2311. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 protrudes from the positive electrode collector 2311 coated with the positive electrode active material layer 2312. The positive electrode collector 2311 not coated with the positive electrode active material layer 2312 serves as a positive electrode tab.
[0098] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer is coated on the surface of the negative electrode current collector, the negative electrode current collector not coated with the negative electrode active material layer protrudes from the negative electrode current collector coated with the negative electrode active material layer, and the negative electrode current collector not coated with the negative electrode active material layer serves as a negative electrode tab. The material of the negative electrode current collector may be copper, and the negative electrode active material may be carbon or silicon, etc. In order to ensure that a large current passes without melting, the number of positive electrode tabs is multiple and stacked together, and the number of negative electrode tabs is multiple and stacked together. The material of the isolation film may be PP (polypropylene) or PE (polyethylene), etc. In addition, the electrode assembly 23 may be a wound electrode assembly or a laminated electrode assembly, and the embodiments of the present application are not limited thereto.
[0099] Figure 5 This is a first structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application. Figure 6 A second structural schematic diagram of the positive electrode sheet 231 provided in some embodiments of the present application; see Figure 5 and Figure 6 , an embodiment of the present application provides a positive electrode sheet 231, the positive electrode sheet 231 includes a positive electrode collector 2311 and a positive electrode active material layer 2312, the positive electrode active material layer 2312 is arranged on at least one surface of the positive electrode collector 2311, the positive electrode active material layer 2312 includes a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b, the first positive electrode active material layer 2312a is arranged between the second positive electrode active material layer 2312b and the positive electrode collector 2311, the first positive electrode active material layer 2312a includes a first positive active material, the second positive electrode active material layer 2312b includes a second positive active material, and the liquid absorption rate of the first positive active material is greater than the liquid absorption rate of the second positive active material.
[0100] The material of the positive electrode current collector 2311 can be one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. Figure 5 In one embodiment, a first positive electrode active material layer 2312a and a second positive electrode active material layer 2312b are sequentially disposed on one surface of the positive electrode current collector 2311; please continue to refer to Figure 6 In another embodiment, the first positive electrode active material layer 2312 a and the second positive electrode active material layer 2312 b are sequentially disposed on both surfaces of the positive electrode current collector 2311 .
[0101] For lithium-ion batteries, the first positive electrode active material and the second positive electrode active material in the first positive electrode active material layer and the second positive electrode active material layer refer to substances capable of intercalating and deintercalating lithium ions.
[0102] The liquid absorption rate of the positive electrode material refers to the absorption rate of the electrolyte by the positive electrode material. The liquid absorption rate of the positive electrode material is mainly affected by its own lattice characteristics. For example, the liquid absorption rate of the layered structure positive electrode material is usually greater than that of the olivine structure positive electrode material. At the same time, in order to pursue better kinetic performance, the kinetic performance is usually improved by controlling the particle size of the positive electrode material, and the particle size will affect the liquid absorption rate of the active material layer composed of the positive electrode material. For example, since the layered structure material is a two-dimensional channel, it has good kinetic performance itself, so its particles are usually larger, and the active material layer composed of larger particles generally has more pores, which is also beneficial to the liquid absorption rate of the active material layer; for example, the olivine structure material is a one-dimensional channel, and its own kinetic performance is relatively poor, so its particles are usually smaller, and the pores of the active material layer composed of smaller particles are generally smaller, and the liquid absorption rate of the active material layer is relatively poor. The liquid absorption rate test of the positive electrode material can be as follows: weigh 2.0g of positive electrode active material powder and place it in the mold of the UTM7305 electronic pressure testing machine, adjust the pressure to 3 tons, maintain the pressure for 30s, dry the mold at 80℃ for 4H, select a capillary with an inner diameter of d=200um, absorb the electrolyte h=3mm, and contact it with the powder in the mold, observe with a microscope and use a stopwatch to time, when the page is completely lowered, read the liquid absorption time t, and calculate the liquid absorption rate v, v=π*(d / 2) 2 *h*ρ / t, where ρ is the density of the electrolyte. The electrolyte density selected for the test in this application is 1.08 g / ml. The test process of the liquid absorption rate of the positive electrode active material in a certain layer of the positive electrode sheet 231 can be that the thickness of each positive electrode material active layer is obtained through an electron microscope image, and the positive electrode active material layer 2312 to be tested is peeled off according to the thickness information, and then immersed in the solvent NMP to wash out the binder therein to obtain the positive electrode active material to be tested, and then the above method is used to test the liquid absorption rate of the positive electrode active material to be tested.
[0103] The positive electrode sheet 231 is formed by placing the first positive electrode active material with a higher liquid absorption rate in the inner layer and the second positive electrode active material with a lower liquid absorption rate in the outer layer. When used as a battery, the second positive electrode active material in the outer layer has a larger contact area with the electrolyte and is closer to the electrolyte, which can shorten the wetting time of the second positive electrode active material with a lower liquid absorption rate; while the first positive electrode active material in the inner layer has a higher liquid absorption rate, which can make up for its short distance from the electrolyte and still achieve wetting in a shorter time, thereby improving the wetting time of the entire positive electrode sheet 231. At the same time, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current unevenness between the first positive electrode active material and the second positive electrode active material, thereby making the positive electrode sheet 231 have a higher capacity retention rate in the early stage of the cycle.
[0104] In the technical solutions of some embodiments of the present application, the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: ab≥1 μg / s.
[0105] By controlling the difference between the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material to exceed 1 μg / s, the first positive electrode active material with a larger liquid absorption rate in the inner layer can help the second positive electrode active material with a smaller liquid absorption rate in the outer layer to achieve infiltration from the inside after being fully infiltrated, thereby further shortening the infiltration time of the entire positive electrode sheet 231.
[0106] Exemplarily, the difference ab between the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material can be 1 μg / s, 1.5 μg / s, 2 μg / s, 2.5 μg / s, 3 μg / s, 3.5 μg / s, 4 μg / s, 4.5 μg / s, 5 μg / s, 5.5 μg / s, 6 μg / s, 6.5 μg / s, 7 μg / s, 7.5 μg / s, 8 μg / s, 8.5 μg / s, 9 μg / s, 9.5 μg / s or 10 μg / s, etc., and it can also be any value within the range of not less than 1 μg / s.
[0107] In the technical solutions of some embodiments of the present application, the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: 2μg / s≤ab≤4μg / s. The difference between the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material is in the range of 2~4μg / s, which can further increase the effect of the first positive electrode active material with a larger liquid absorption rate in the inner layer helping the second positive electrode active material with a smaller liquid absorption rate in the outer layer to achieve wetting from the inside. At the same time, it can reduce the possibility that the first positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate failing to achieve good wetting.
[0108] In the technical solutions of some embodiments of the present application, the second positive electrode active material layer 2312b includes a first region and a second region, the first region includes the second positive electrode active material, the second region includes the third positive electrode active material, and the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: c>b. By using the third positive electrode active material with a larger liquid absorption rate and the second positive electrode active material with a smaller liquid absorption rate to form the second positive electrode active material layer 2312b, the third positive electrode active material with a larger liquid absorption rate can accelerate the infiltration of the second positive electrode active material layer 2312b. At the same time, to a certain extent, it can also help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration, further accelerating the infiltration of the second positive electrode active material layer 2312b.
[0109] In the technical solutions of some embodiments of the present application, the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: cb≥1μg / s; optionally, the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5μg / s≤cb≤5μg / s. By controlling the difference between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not less than 1μg / s, the third positive electrode active material with a larger liquid absorption rate can better help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration. At the same time, controlling the difference between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not more than 5μg / s can reduce the possibility that the third positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate being unable to achieve good infiltration.
[0110] Exemplarily, the difference cb between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material can be 1μg / s, 1.5μg / s, 2μg / s, 2.5μg / s, 3μg / s, 3.5μg / s, 4μg / s, 4.5μg / s, 5μg / s, 5.5μg / s, 6μg / s, 6.5μg / s, 7μg / s, 7.5μg / s, 8μg / s, 8.5μg / s, 9μg / s, 9.5μg / s or 10μg / s, etc., and it can also be any value within the range of not less than 1μg / s.
[0111] In the technical solutions of some embodiments of this application, please refer to Figure 7 , Figure 7 This is a schematic structural diagram of the second positive electrode active material layer 2312b provided in some embodiments of the present application, where the second region is located in the central region C of the second positive electrode active material layer 2312b.
[0112] The central region C refers to the region near the central axis of the second positive electrode active material layer 2312b. The central axis of the central region C may coincide with the central axis of the second positive electrode active material layer 2312b, or may be slightly offset. The contour shape of the central region C may match the second positive electrode active material layer 2312b. For example, if the contour of the first positive electrode active material layer 2312a is rectangular, the contour of the central region C is also rectangular. If the contour of the first positive electrode active material layer 2312a is circular, the contour of the central region C is also circular. Alternatively, the contour shape may be any other shape without being affected by the second positive electrode active material layer 2312b. For example, if the contour of the first positive electrode active material layer 2312a is rectangular, the contour of the central region C is circular. If the contour of the first positive electrode active material layer 2312a is circular, the contour of the central region C is rectangular.
[0113] By placing the third positive electrode active material with a higher liquid absorption rate in the central region C of the second positive electrode active material layer 2312b, which is relatively difficult to wet, its higher liquid absorption rate can make up for the difficulty of wetting the central region C, so that the entire second positive electrode active material layer 2312b can be wetted more synchronously. At the same time, the regional arrangement can reduce the mutual influence between the third positive electrode active material and the second positive electrode active material, which is beneficial to battery performance.
[0114] In the technical solutions of some embodiments of this application, please refer to Figure 8 , Figure 8 A third structural schematic diagram of the positive electrode sheet 231 provided for some embodiments of the present application; the positive electrode active material layer 2312 also includes a third positive electrode active material layer 2312c, and the third positive electrode active material layer 2312c is arranged on the surface of the second positive electrode active material layer 2312b away from the first positive electrode active material layer 2312a, and the third positive electrode active material layer 2312c includes a fourth positive electrode active material, and the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: d>b.
[0115] It should be noted that when the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b are arranged on both sides of the positive electrode collector, the third positive electrode active material layer 2312c can be arranged on the second positive electrode active material layer 2312b on either side, or can be arranged on the second positive electrode active material layer 2312b on both sides at the same time.
[0116] By disposing a third positive electrode active material layer 2312c outside the second positive electrode active material layer 2312b containing the second positive electrode active material with a lower liquid absorption rate, the third positive electrode active material layer 2312c contains a fourth positive electrode active material with a larger liquid absorption rate. After being fully infiltrated with the first positive electrode active material layer 2312a, the third positive electrode active material layer 2312c can simultaneously help the second positive electrode active material layer 2312b to be infiltrated from both sides of the second positive electrode active material layer 2312b, thereby shortening the infiltration time of the entire positive electrode sheet 231.
[0117] In the technical solutions of some embodiments of the present application, the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: db≥1μg / s; optionally, the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5μg / s≤db≤5μg / s. By controlling the difference between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not less than 1μg / s, the fourth positive electrode active material with a larger liquid absorption rate can better help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration. At the same time, controlling the difference between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material to be not more than 5μg / s can reduce the possibility that the fourth positive electrode active material with a larger liquid absorption rate absorbs too much electrolyte, resulting in the second positive electrode active material with a smaller liquid absorption rate being unable to achieve good infiltration.
[0118] Exemplarily, the difference db between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material can be 1μg / s, 1.5μg / s, 2μg / s, 2.5μg / s, 3μg / s, 3.5μg / s, 4μg / s, 4.5μg / s, 5μg / s, 5.5μg / s, 6μg / s, 6.5μg / s, 7μg / s, 7.5μg / s, 8μg / s, 8.5μg / s, 9μg / s, 9.5μg / s or 10μg / s, etc., and it can also be any value within the range of not less than 1μg / s.
[0119] In the technical solutions of some embodiments of the present application, the ultimate compaction density of the first positive electrode active material is 3.4-3.75 g / cm 3 ; The ultimate compaction density of the second positive electrode active material is 2.1~2.4 g / cm 3 ; The ultimate compaction density of the third positive electrode active material is 3.4~3.75 g / cm 3 ; The ultimate compaction density of the fourth positive electrode active material is 3.4~3.75 g / cm 3 .
[0120] The ultimate compaction density refers to the maximum compaction density that a material can withstand in the layer in which it is located, which reflects the pressure resistance of the material to a certain extent. The test method of the ultimate compaction density is: first, place the material to be tested on the current collector and roll it to a smaller compaction density, and specify the position and angle of the fold, then use a fixed pressure to flatten it, observe the fold of the pole piece after folding, gradually increase the flattening pressure and repeat the above steps, and finally when the flattening pressure reaches a certain value, the pole piece will break or have a light-transmitting hole, then the highest flattening pressure without breakage and light-transmitting hole corresponds to the compaction density as the ultimate compaction density.
[0121] Generally, the ultimate compaction density of the positive electrode active material is positively correlated with its liquid absorption rate. The greater the ultimate compaction density, the greater the liquid absorption rate. The ultimate compaction density is 2.1~2.4g / cm 3 The second positive electrode active material can have a limiting compaction density of 3.4~3.75g / cm 3 The first positive electrode active material with a maximum compaction density of 3.4-3.75 g / cm 3 The third positive electrode active material and the ultimate compaction density are 3.4~3.75g / cm 3 A good liquid absorption rate difference is formed between the fourth positive electrode active materials, thereby shortening the wetting time of the entire electrode.
[0122] For example, the ultimate compaction density of the first positive electrode active material may be 3.4 g / cm 3 、3.45 g / cm 3 , 3.5g / cm 3 、3.55 g / cm 3 、3.6 g / cm 3 、3.65 g / cm 3 、3.7 g / cm 3 or 3.75 g / cm 3 , which can also be 3.4~3.75g / cm 3 The second positive electrode active material may have a maximum compaction density of 2.1 g / cm 3 , 2.15 g / cm 3 , 2.2g / cm 3 , 2.25 g / cm 3 , 2.3 g / cm 3 , 2.35 g / cm 3 or 2.4 g / cm 3 , which can also be 2.1~2.4g / cm 3 The third positive electrode active material may have a maximum compaction density of 3.4 g / cm 3 、3.45 g / cm 3, 3.5 g / cm 3 、3.55 g / cm 3 、3.6 g / cm 3 , 3.65 g / cm 3 、3.7 g / cm 3 or 3.75 g / cm 3 , which can also be 3.4~3.75g / cm 3 The fourth positive electrode active material may have a maximum compaction density of 3.4 g / cm 3 , 3.45 g / cm 3 , 3.5g / cm 3 、3.55 g / cm 3 、3.6 g / cm 3 、3.65 g / cm 3 、3.7 g / cm 3 or 3.75 g / cm 3 , which can also be 3.4~3.75g / cm 3 Any value in the range.
[0123] In the technical solutions of some embodiments of the present application, the ultimate compaction density of the first positive electrode active material is 3.55-3.7 g / cm 3 The second positive electrode active material has a limiting compaction density of 2.25-2.4 g / cm 3 The ultimate compaction density of the third positive electrode active material is 3.55~3.7g / cm 3 ; The ultimate compaction density of the fourth positive electrode active material is 3.55~3.7g / cm 3 .
[0124] In the technical solutions of some embodiments of the present application, the first positive electrode active material includes a ternary system material; the second positive electrode active material includes a polyanion positive electrode material; the third positive electrode active material includes a ternary system material; and the fourth positive electrode active material includes a ternary system material.
[0125] Ternary system materials usually include two types: NCA and NCM. Among them, NCA is widely used due to its long life, large capacity, and high energy density; while NCM combines the advantages of three types of positive electrode materials: lithium cobalt oxide, lithium nickel oxide, and lithium manganese oxide, and has an obvious ternary synergistic effect.
[0126] Polyanion positive electrode materials are a general term for a series of compounds containing tetrahedral or octahedral anion structural units (XOm)n-. They have the advantages of high charge and discharge voltage, large energy storage capacity, fast charge and discharge capability and good cycle stability. Their synthesis methods mainly include: high temperature solid phase method, sol-gel method, hydrothermal method, electrospinning method, etc.
[0127] Polyanion positive electrode materials usually exhibit good safety performance, and ternary system materials usually exhibit higher energy density. Using polyanion positive electrode materials as the second positive electrode active material and ternary system materials as the first positive electrode active material can make the positive electrode sheet 231 have both higher safety performance and higher energy density.
[0128] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes at least one of lithium iron phosphate, lithium manganese phosphate and LiMPO4, and M in LiMPO4 includes Mn and non-Mn elements.
[0129] It should be noted that the above-mentioned LiMPO4 is not a specific molecular structure formula, but a general expression of lithium manganese-containing phosphate.
[0130] In the technical solutions of some embodiments of the present application, the non-Mn element includes one or both of a first doping element and a second doping element, the first doping element is manganese-doped, and the second doping element is phosphorus-doped.
[0131] In the technical solutions of some embodiments of the present application, the first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge.
[0132] In the technical solutions of some embodiments of the present application, the first doping element includes at least two of Fe, Ti, V, Ni, Co and Mg.
[0133] In the technical solutions of some embodiments of the present application, the second doping element includes one or more elements selected from the group consisting of B, S, Si and N.
[0134] In the technical solutions of some embodiments of the present application, the second positive electrode active material includes Li 1+x Mn 1-y A y P 1-z R z O4, Li 1+x Mn 1-y A y P 1-z R z In O4, x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
[0135] In the technical solutions of some embodiments of the present application, the compound Li 1+x Mn 1-y AHr 1-z The preparation method of RzO4 may include the following steps:
[0136] (1) dissolving a manganese source, a source of an element A to be doped at the manganese position, and an acid in a solvent and stirring to generate a suspension of a manganese salt doped with the element A, filtering the suspension and drying the filter cake to obtain a manganese salt doped with the element A;
[0137] (2) adding a lithium source, a phosphorus source, an element R source, a solvent and the manganese salt doped with element A obtained in step (1) into a reaction container, grinding and mixing to obtain a slurry;
[0138] (3) transferring the slurry obtained in step (2) to a spray drying device for spray drying and granulation to obtain granules;
[0139] (4) Sintering the particles obtained in step (3) to obtain a positive electrode active material.
[0140] In any embodiment, the manganese source may be a manganese-containing substance known in the art that can be used to prepare lithium manganese phosphate. For example, the manganese source may be selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, manganese carbonate, or a combination thereof.
[0141] The acid is selected from one or more of hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, organic acid such as oxalic acid, etc., for example, oxalic acid. The source of element R is selected from at least one of sulfate, borate, nitrate and silicate of element R. The source of element A is selected from at least one of simple substance, oxide, phosphate, oxalate, carbonate and sulfate of A.
[0142] In the technical solutions of some embodiments of the present application, the polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k C k O 4- l D l, wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
[0143] It should be noted that Li h A i Mn 1-j B j P 1-k C k O 4-l D l The compound is actually a specific LiMPO4 material. Its preparation method can refer to Li 1+x Mn 1-y A y P 1-z R z O4, no limitation is made here.
[0144] Below is Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 The preparation process is further explained: 1. Preparation of doped manganese oxalate: 1.3 mol of MnSO4﹒H2O and 0.7 mol of FeSO4﹒H2O are fully mixed in a mixer for 6 hours. The mixture is transferred to a reactor, and 10L of deionized water and 2 mol of dihydrated oxalic acid (calculated as oxalic acid) are added. The reactor is heated to 80°C and stirred at 600 rpm for 6 hours. The reaction is terminated (no bubbles are generated) to obtain a Fe-doped manganese oxalate suspension. The suspension is then filtered, the filter cake is dried at 120°C, and then ground to obtain a median particle size Dv 50Fe-doped manganese oxalate particles of about 100 nm. 2. Preparation of doped lithium manganese phosphate: Take 1 mol of the above manganese oxalate particles, 0.497 mol of lithium carbonate, 0.001 mol of Mo(SO4)3, an aqueous phosphoric acid solution containing 0.999 mol of phosphoric acid at a concentration of 85%, 0.001 mol of H4SiO4, 0.0005 mol of NH4HF2 and 0.005 mol of sucrose and add them to 20L of deionized water. Transfer the mixture to a sand mill and grind and stir it for 10 hours to obtain a slurry. Transfer the slurry to a spray drying equipment for spray drying and granulation, set the drying temperature to 250°C, dry for 4 hours, and obtain particles. In a protective atmosphere of nitrogen (90% volume) + hydrogen (10% volume), sinter the above powder at 700°C for 10 hours to obtain carbon-coated Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 Si 0.001 O 3.999 F 0.001 .
[0145] In the technical solutions of some embodiments of the present application, the second positive electrode active material further has a carbon-containing coating layer.
[0146] The introduction of the carbon-containing coating layer improves the conductivity of the positive electrode active material. At this time, the structure of the positive electrode active material is actually a core-shell structure with LiMPO4 as the core and the surface of the core covered with the coating layer.
[0147] In the technical solutions of some embodiments of the present application, the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material is 1%~3%; optionally, the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material is 1.5%~2.5%.
[0148] By controlling the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material to 1% to 3%, the second positive electrode active material has a better liquid absorption rate. At the same time, the energy density of the electrode can also be taken into account.
[0149] Exemplarily, the mass proportion of the carbon-containing coating layer in the polyanion positive electrode material can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8% or 3%, etc., and it can also be any value in the range of 1% to 3%.
[0150] In the list of positive electrode materials in this application, the molar content of Li is the initial state of the material, that is, the state before adding the materials. The positive electrode material is used in the battery system, and the molar content of Li will change after charge and discharge cycles.
[0151] In addition, due to the different preparation processes and conditions of the materials, the molar content of the O element is usually not strictly the coefficient of the O element in the chemical formula, and there will be fluctuations, such as Li 1+x Mn 1-y A y P 1-z R z The molar content of the O element in O4 is not strictly 4.
[0152] For example, the second positive electrode active material may be LiFePO4, LiMn 0.1 Fe 0.9 PO4、LiMn 0.2 Fe 0.8 PO4、LiMn 0.3 Fe 0.7 PO4、LiMn 0.4 Fe 0.6 PO4、LiMn 0.5 Fe 0.5 PO4、LiMn 0.6 Fe 0.4 PO4、LiMn 0.7 Fe 0.3 PO4、LiMn 0.8 Fe 0.2 PO4、LiMn 0.9 Fe 0.1 PO4, LiMnPO4, LiMn 0.5 Al 0.5 P 0.5 B 0.5 O4、LiMn 0.5 Mg 0.5 P 0.5 S 0.5 O4, etc., M in LiMPO4 includes Mn and non-Mn elements, non-Mn elements include one or two of the first doping element and the second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping. The first doping element includes one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; the second doping element includes one or more elements of B, S, Si and N.
[0153] In the technical solutions of some embodiments of the present application, the ternary system materials include nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials. Among them, the ternary system materials include nickel-cobalt-manganese ternary materials and their modified materials and nickel-cobalt-aluminum ternary materials and their modified materials.
[0154] In the technical solutions of some embodiments of the present application, the ternary system material includes Li a Nib Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is selected from one or both elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
[0155] Exemplarily, the ternary system material can be LiNi 0.4 Co 0.2 Mn 0.4 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2 and LiNi 0.7 Co 0.15 Mn 0.15 O2, etc. Li a Ni b Co c M1 d M2 e O f R g In LiNiCoM1M2OR, a can be any one or more values within the range of 0.75 to 1.2, b can be any one or more values within the range of 0.3 to 1.0, c can be any one or more values within the range of 0 to 0.4, d can be any one or more values within the range of 0 to 1, e can be any one or more values within the range of 0 to 0.2, f can be any value within the range of 1 to 2.5, and g can be any one or more values within the range of 0 to 1.
[0156] It should be noted that the above listing of the first positive electrode active material and the second positive electrode active material is only for illustrative purposes to show that the present solution can be implemented, and is not intended to limit the present solution. In other embodiments, those skilled in the art can select the specific substances of the first positive electrode active material and the second positive electrode active material according to actual needs, such as the above-listed materials and their modified substances, and the modification includes doping or coating, etc.
[0157] After introducing the material and structure of the positive electrode sheet 231 as described above, the preparation method of the positive electrode sheet 231 will be specifically introduced below.
[0158] The method for preparing the positive electrode sheet 231 containing only the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b includes the following steps: coating the first positive electrode active slurry on the surface of the positive electrode current collector 2311 to form the first positive electrode active material layer 2312a. Coating the second positive electrode active slurry on the surface of the first positive electrode active material layer 2312a to form the second positive electrode active material layer 2312b. The liquid absorption rate a of the first positive electrode active material in the first positive electrode active slurry and the liquid absorption rate b of the second positive electrode active material in the second positive electrode active slurry satisfy the following relationship: ab≥1μg / s.
[0159] The method is to place the first positive electrode active material with a higher liquid absorption rate in the inner layer and the second positive electrode active material with a lower liquid absorption rate in the outer layer. When used as a battery, the second positive electrode active material in the outer layer has a larger contact area with the electrolyte and is closer to the electrolyte, which can shorten the wetting time of the second positive electrode active material with a lower liquid absorption rate; while the first positive electrode active material in the inner layer has a higher liquid absorption rate, which can make up for its shortcoming of being far away from the electrolyte and can still achieve wetting in a shorter time, thereby improving the wetting time of the entire positive electrode sheet 231. At the same time, by controlling the difference in the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material to exceed 1 μg / s, the first positive electrode active material in the inner layer with a higher liquid absorption rate can help the second positive electrode active material in the outer layer with a lower liquid absorption rate to achieve wetting from the inside after being fully wetting, further shortening the wetting time of the entire positive electrode sheet 231. Furthermore, arranging the first positive electrode active material and the second positive electrode active material in layers can reduce the possibility of current non-uniformity between the first positive electrode active material and the second positive electrode active material, thereby enabling the positive electrode sheet 231 to have a higher capacity retention rate in the early stage of the cycle.
[0160] When the second positive electrode active material layer 2312b of the aforementioned positive electrode sheet 231 contains not only the second positive electrode active material but also the third positive electrode active material, the preparation of the second positive electrode active material layer 2312b includes the following steps: the second positive electrode active material and the third positive electrode active material are respectively formulated into a second positive electrode active slurry and a third positive electrode active slurry, the third positive electrode active slurry is applied to the central area C, and then the second positive electrode active slurry is applied to the remaining area to form the second positive electrode active material layer 2312b together.
[0161] The method forms the second positive electrode active material layer 2312b by using a third positive electrode active material with a larger liquid absorption rate and a second positive electrode active material with a smaller liquid absorption rate. The third positive electrode active material with a larger liquid absorption rate can accelerate the infiltration of the second positive electrode active material layer 2312b. At the same time, to a certain extent, it can also help the second positive electrode active material with a smaller liquid absorption rate to achieve infiltration, further accelerating the infiltration of the second positive electrode active material layer 2312b. At the same time, the third positive electrode active material with a larger liquid absorption rate is arranged in the central area C of the second positive electrode active material layer 2312b, which is relatively difficult to achieve infiltration. Its larger liquid absorption rate can make up for the difficulty of infiltration in the central area C, so that the entire second positive electrode active material layer 2312b can achieve overall infiltration more synchronously. At the same time, the regional arrangement can reduce the mutual influence between the third positive electrode active material and the second positive electrode active material, which is beneficial to the battery performance.
[0162] When the aforementioned positive electrode sheet 231 also includes a third positive electrode active material layer 2312c, after completing the preparation of the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b according to the above method, the fourth positive electrode active material is prepared into a fourth positive electrode active slurry, and the fourth positive electrode active slurry is coated on the surface of the second positive electrode active material layer 2312b to form the third positive electrode active material layer 2312c.
[0163] The method is carried out by arranging a third positive electrode active material layer 2312c outside a second positive electrode active material layer 2312b containing a second positive electrode active material with a lower liquid absorption rate. The third positive electrode active material layer 2312c contains a fourth positive electrode active material with a larger liquid absorption rate. After being fully infiltrated with the first positive electrode active material layer 2312a, the third positive electrode active material layer 2312c can simultaneously help the second positive electrode active material layer 2312b to be infiltrated from both sides of the second positive electrode active material layer 2312b, thereby shortening the infiltration time of the entire positive electrode sheet 231.
[0164] The following is an example of a method for preparing a positive electrode sheet 231 containing only a first positive electrode active material layer 2312 a and a second positive electrode active material layer 2312 b .
[0165] Fig. 9 For a flow chart of a method for preparing the positive electrode sheet 231 provided in some embodiments of the present application, please refer to Fig. 9 The present application embodiment provides a method for preparing a positive electrode sheet 231, the method comprising:
[0166] S110, preparing a first positive electrode active slurry: dispersing a first positive electrode active material, a binder and a conductive agent in a solvent to form a first positive electrode active slurry. The first positive electrode active material may be the first positive electrode active material described above, for example, a material having a chemical formula of LiNix Co y Mn z O2, (0≤x≤1, 0≤y≤1, 0≤z≤1, x+y+z=1) ternary system material, optionally, a small amount of other positive electrode active materials may be added.
[0167] For the specific selection of the ternary system material, reference may be made to the selection of the ternary system material in the first positive electrode active material layer 2312 a in the aforementioned positive electrode sheet 231 , which will not be described in detail here.
[0168] The binder may be one or more of styrene-butadiene rubber, water-based acrylic resin, carboxymethyl cellulose, polyvinylidene fluoride, polytetrafluoroethylene, ethylene-vinyl acetate copolymer, polyvinyl alcohol and polyvinyl butyral. The conductive agent may be at least one of conductive carbon black, carbon fiber, carbon nanotube, Ketjen black, graphene or acetylene black. The solvent may be one or more of dimethyl glutarate and N-methyl pyrrolidone. A leveling agent, a dispersant, etc. may also be added to the first positive electrode active slurry.
[0169] S120, preparing a second positive electrode active slurry: dispersing a second positive electrode active material, a binder and a conductive agent in a solvent to form a second positive electrode active slurry. The second positive electrode active material may be the second positive electrode active material described above, for example, a material having a chemical formula of LiMn a Fe 1-a PO4, (0≤a≤1) polyanion positive electrode material, optionally, a small amount of other positive electrode active materials may be added.
[0170] For the specific selection of the polyanion positive electrode material, reference may be made to the selection of the polyanion positive electrode material in the second positive electrode active material layer 2312 b in the aforementioned positive electrode sheet 231 , which will not be described in detail here.
[0171] The binder, the conductive agent and the solvent may be the binder, the conductive agent and the solvent in the first positive electrode active slurry, etc. The binder in the first positive electrode active slurry may be the same as or different from the binder in the second positive electrode active material; the conductive agent in the first positive electrode active slurry may be the same as or different from the conductive agent in the second positive electrode active material; the solvent in the first positive electrode active slurry may be the same as or different from the solvent in the second positive electrode active material. At the same time, a leveling agent, a dispersant, etc. may also be added to the second positive electrode active slurry, which is not limited in this application.
[0172] S130, preparing the first positive electrode active material layer 2312a: coating the first positive electrode active slurry on the surface of the positive electrode current collector 2311, and then drying to form the first positive electrode active material layer 2312a. The coating can be applied to one surface or both surfaces of the positive electrode current collector 2311 according to requirements.
[0173] The coating method may be: scraping, roller coating, slit coating, etc., which is not limited in this application. It should be noted that step S120 and step S130 can be interchanged or performed simultaneously, which is not limited in this application.
[0174] S140, preparing the second positive electrode active material layer 2312b: coating the second positive electrode active slurry on the surface of the first positive electrode active material layer 2312a, and then drying to form the second positive electrode active material layer 2312b. During coating, the second positive electrode active material layer 2312b can be formed on the surface of the first positive electrode active material layer 2312a according to the situation of the first positive electrode active material layer 2312a.
[0175] S150 , rolling the second positive electrode active material layer 2312 b to obtain the positive electrode sheet 231 .
[0176] It should be noted that the above is only an example of sequentially arranging the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b on the positive electrode current collector 2311. In other embodiments, the first positive electrode active material layer 2312a and the second positive electrode active material layer 2312b can be exchanged.
[0177] After the positive electrode sheet 231 is prepared, the first isolation film, the positive electrode sheet 231, the second isolation film and the negative electrode sheet are stacked in sequence, wound to form a wound flat structure, and then hot pressed to obtain a wound electrode assembly; or, after the positive electrode sheet 231 is prepared, the positive electrode sheet 231, the isolation film, the negative electrode sheet, the isolation film, and so on, are stacked in sequence to form a stacked electrode assembly.
[0178] The electrode assembly 23 can be used to prepare a battery cell 20 , and the battery cell 20 can be used to prepare a secondary battery 100 and provide electric energy to an electric device.
[0179] Next, one or more embodiments are described in more detail with reference to the following examples. Of course, these examples do not limit the scope of one or more embodiments.
[0180] Examples and Comparative Examples
[0181]
Preparation of positive electrode
[0182] 1) A positive electrode sheet containing only the first positive electrode active material layer and the second positive electrode active material layer
[0183] ① The second positive electrode active material layer contains only the second positive electrode active material
[0184] Preparation of the first positive electrode active material layer: The first positive electrode active material LiNi 0.55 Co 0.12 Mn 0.32V 0.01 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain the first coating layer slurry; then the slurry was mixed at 90mg / 1540.25mm 2 The mass of the positive electrode active material is evenly coated on the positive electrode current collector and dried to obtain a first positive electrode active material layer.
[0185] Preparation of the second positive electrode active material layer: The second positive electrode active material LiMn 0.6 Fe 0.4 Na 0.01 PO4, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain a second coating layer slurry; then the slurry was added at 200 mg / 1540.25 mm 2 The mass is evenly coated on the first positive electrode active material layer, and after drying, it is rolled and die-cut to obtain a lithium-ion battery positive electrode sheet.
[0186] ② The second positive electrode active material layer contains the second positive electrode active material and the third positive electrode active material
[0187] Preparation of the first positive electrode active material layer: The first positive electrode active material LiNi 0.55 Co 0.12 Mn 0.32 V 0.01 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain the first coating layer slurry; then the slurry was mixed at 90mg / 1540.25mm 2 The mass of the positive electrode active material is evenly coated on the positive electrode current collector and dried to obtain a first positive electrode active material layer.
[0188] Preparation of the second positive electrode active material layer: The second positive electrode active material LiMn 0.6 Fe 0.4 Na 0.01 PO4, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain a second coating layer slurry. The third positive electrode active material LiNi 0.55 Co 0.12 Mn 0.33 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain a third coating slurry; then the third coating slurry was added at 200 mg / 1540.25 mm2 The mass of the second coating slurry was uniformly coated on the central area of the first positive electrode active material layer, and the second coating slurry was uniformly coated on the central area of the first positive electrode active material layer at 200 mg / 1540.25 mm 2 The mass of the positive electrode active material is evenly coated on the remaining area on the first positive electrode active material layer, and the second positive electrode active material layer is obtained after drying, and the positive electrode sheet of the lithium ion battery is obtained after rolling and die cutting.
[0189] 2) The positive electrode sheet includes a first positive electrode active material layer, a second positive electrode active material layer and a third positive electrode active material layer
[0190] Prepare a first positive electrode active material layer and a second positive electrode active material layer according to the above method;
[0191] Preparation of the third positive electrode active material layer: The fourth positive electrode active material LiNi 0.55 Co 0.12 Mn 0.32 V 0.01 O2, conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) were added to N-methylpyrrolidone (NMP) at a mass ratio of 90:5:5, and stirred and mixed to obtain a fourth coating layer slurry; then the slurry was added at 90mg / 1540.25mm 2 The mass of the positive electrode active material is evenly coated on the second positive electrode active material layer, dried to obtain the third positive electrode active material layer, and then rolled and die-cut to obtain the lithium-ion battery positive electrode sheet.
[0192]
Preparation of negative electrode sheet
[0193] The active material artificial graphite, the conductive agent carbon black, the binder styrene-butadiene rubber (SBR), and the thickener sodium hydroxymethyl cellulose (CMC) are dissolved in the solvent deionized water in a mass ratio of 95:2:1:2, and mixed evenly to prepare a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil once or multiple times, and the negative electrode sheet is obtained after drying, cold pressing, and slitting.
[0194]
Preparation of electrolyte
[0195] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), the organic solvents ethylene carbonate (EC) / diethyl carbonate (DEC) / ethyl methyl carbonate (EMC) were mixed evenly in a volume ratio of 1 / 1 / 1, 1 mol / L LiPF6 lithium salt was added and dispersed evenly, and then 5% fluoroethylene carbonate was dissolved in the above organic solvents and stirred evenly to obtain an electrolyte.
[0196]
Isolation film
[0197] A polyethylene film was used as the separator, and its thickness was 7 μm.
[0198]
Preparation of secondary batteries
[0199] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are wound to form the corresponding battery cell, and the battery cell is hot pressed at 90°C, followed by ultrasonic welding of the positive and negative electrode tabs. The positive electrode uses aluminum tabs, and the negative electrode uses copper tabs. The positive and negative electrode tabs are located on the same side of the battery cell. The battery cell after the tab welding is placed in an aluminum shell of appropriate size for soft connection and top cover welding. The battery cell is vacuum dried at 175°C for 24 hours, and then the electrolyte is injected and sealed to obtain an uncharged battery. The uncharged battery then undergoes the processes of static, formation, aging, exhaust, secondary sealing, capacity testing, etc. to obtain a secondary battery.
[0200] The main parameters of each embodiment and comparative example are shown in the following table:
[0201]
[0202] “ / ” in the table means that the material is not contained, so it is not limited and the corresponding preparation steps are not performed.
[0203] The performance test was performed on the batteries provided in each embodiment and comparative example, and the performance test specifically included:
[0204] Wetting time test: In the secondary battery preparation process, the length of the positive electrode sheet is ensured to be 6000mm for the uninjected battery cell. Under a constant temperature environment of 25℃, the electrolyte (density 1.08g / ml, viscosity 5Pa·S) is added into the battery cell. At this time, the timing is started to ensure that the filling coefficient is 3g / Ah. At the same time, the battery cell is photographed with X-ray. When it is confirmed that the inside of the battery cell has been completely infiltrated and the color of the electrode sheet under the X-ray is uniform and there is no uninfiltrated area, the timing is stopped. The timing time T is the infiltration time.
[0205] The test results are shown in the following table:
[0206]
[0207] It can be seen from the above table that the electrode of the secondary battery provided by the embodiment of the present application can achieve better wetting in a shorter time.
[0208] By comparing Examples 4 to 9 with Comparative Examples 1 to 2, it can be seen that as the difference in liquid absorption rate between the first positive electrode active material and the second positive electrode active material increases, the wetting time of the electrode sheet shows a trend of first decreasing and then increasing. When the difference in liquid absorption rate between the first positive electrode active material and the second positive electrode active material is greater than 1 μg / s, the wetting time of the electrode sheet can be controlled within 120 min, especially when the difference in liquid absorption rate between the first positive electrode active material and the second positive electrode active material is 2~4 μg / s, the wetting time of the electrode sheet can be controlled within 100 min.
[0209] By comparing Examples 10 to 17 with Example 1, it can be obtained that by placing a third positive electrode active material with a larger liquid absorption rate in the central area and placing a second positive electrode active material with a smaller liquid absorption rate in the remaining area to jointly form a second positive electrode active material layer, the wetting time of the electrode can be further shortened. At the same time, as the difference in liquid absorption rate between the third positive electrode active material and the second positive electrode active material increases, the wetting time of the electrode shows a trend of first decreasing and then increasing. When the difference in liquid absorption rate between the third positive electrode active material and the second positive electrode active material is greater than 1 μg / s, the wetting time of the electrode can be controlled within 60 minutes, especially when the difference in liquid absorption rate between the third positive electrode active material and the second positive electrode active material is between 1.5 and 5 μg / s, the wetting time of the electrode can be controlled within 55 minutes.
[0210] By comparing Examples 18 to 25 with Example 1, it can be obtained that by arranging a third positive electrode active material layer containing a fourth positive electrode active material with a larger liquid absorption rate outside the second positive electrode active material layer containing the second positive electrode active material with a lower liquid absorption rate, the wetting time of the electrode can be further shortened. At the same time, with the increase of the difference in liquid absorption rate between the fourth positive electrode active material and the second positive electrode active material, the wetting time of the electrode shows a trend of first decreasing and then increasing. When the difference in liquid absorption rate between the fourth positive electrode active material and the second positive electrode active material is greater than 1 μg / s, the wetting time of the electrode can be controlled within 62 min, especially when the difference in liquid absorption rate between the fourth positive electrode active material and the second positive electrode active material is 1.5~5 μg / s, the wetting time of the electrode can be controlled within 60 min.
[0211] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer, wherein the positive electrode active material layer is disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer includes a first positive electrode active material layer and a second positive electrode active material layer, wherein the first positive electrode active material layer is disposed between the second positive electrode active material layer and the positive electrode current collector, wherein the first positive electrode active material layer includes a first positive electrode active material, wherein the second positive electrode active material layer includes a second positive electrode active material, wherein the liquid absorption rate a of the first positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfy the following relationship: 2 μg / s≤ab≤4 μg / s; wherein the ultimate compaction density of the first positive electrode active material is 3.4-3.75 g / cm 3 The ultimate compaction density of the second positive electrode active material is 2.1~2.4g / cm 3 ; The first cathode active material is a ternary system material, and the second cathode active material is a polyanion cathode material; The liquid absorption rate test of the first positive electrode active material / the second positive electrode active material is as follows: 2.0 g of the positive electrode active material powder to be tested is weighed and placed in the mold of the UTM7305 electronic pressure testing machine, the pressure is adjusted to 3 tons, and after the pressure is maintained for 30 seconds, the mold is dried at a temperature of 80°C and a drying time of 4 hours. A capillary with an inner diameter d of 200 μm is selected to absorb the electrolyte of h=3 mm, and then contact the powder in the mold, observe with a microscope and time with a stopwatch, and when the electrolyte level has dropped, read the liquid absorption time t, and calculate the liquid absorption rate v, v=π*(d / 2) 2 *h*ρ / t, where ρ is the density of the electrolyte, which is 1.08 g / ml.
2. The positive electrode sheet according to claim 1, characterized in that: The second positive electrode active material layer includes a first region and a second region, the first region includes a second positive electrode active material, the second region includes a third positive electrode active material, and the relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: c>b.
3. The positive electrode sheet according to claim 2, characterized in that: The relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: cb≥1 μg / s.
4. The positive electrode sheet according to claim 3, characterized in that: The relationship between the liquid absorption rate c of the third positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5 μg / s≤cb≤5 μg / s.
5. The positive electrode sheet according to any one of claims 2 to 4, characterized in that: The second region is located in a central region of the second positive electrode active material layer.
6. The positive electrode sheet according to claim 1, characterized in that: The positive electrode active material layer also includes a third positive electrode active material layer, and the third positive electrode active material layer is arranged on the surface of the second positive electrode active material layer away from the first positive electrode active material layer. The third positive electrode active material layer includes a fourth positive electrode active material, and the relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: d>b.
7. The positive electrode sheet according to claim 6, characterized in that: The relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: db≥1 μg / s.
8. The positive electrode sheet according to claim 7, characterized in that: The relationship between the liquid absorption rate d of the fourth positive electrode active material and the liquid absorption rate b of the second positive electrode active material satisfies: 1.5 μg / s≤db≤5 μg / s.
9. The positive electrode sheet according to claim 6, characterized in that: The fourth positive electrode active material has a limiting compaction density of 3.4 to 3.75 g / cm 3 .
10. The positive electrode sheet according to claim 9, characterized in that: The ultimate compaction density of the first positive electrode active material is 3.55-3.7 g / cm 3 ; and / or The ultimate compaction density of the second positive electrode active material is 2.25-2.4 g / cm 3 ; and / or The fourth positive electrode active material has a limiting compaction density of 3.55 to 3.7 g / cm 3 .
11. The positive electrode sheet according to claim 9, characterized in that: The fourth positive electrode active material includes a ternary system material.
12. The positive electrode sheet according to claim 2, characterized in that: The ultimate compaction density of the third positive electrode active material is 3.4-3.75 g / cm 3 .
13. The positive electrode sheet according to claim 12, characterized in that: The ultimate compaction density of the first positive electrode active material is 3.55-3.7 g / cm 3 ; and / or The ultimate compaction density of the second positive electrode active material is 2.25-2.4 g / cm 3 ; and / or The ultimate compaction density of the third positive electrode active material is 3.55-3.7 g / cm 3 .
14. The positive electrode sheet according to claim 12, characterized in that: The third positive electrode active material includes a ternary system material.
15. The positive electrode sheet according to claim 11 or 14, characterized in that: The ternary system materials include nickel-cobalt-manganese ternary materials and modified materials thereof and nickel-cobalt-aluminum ternary materials and modified materials thereof; and / or The polyanion positive electrode material includes LiMPO4, M in LiMPO4 includes Mn and non-Mn elements, the non-Mn elements include one or both of a first doping element and a second doping element, the first doping element is manganese doping, and the second doping element is phosphorus doping.
16. The positive electrode sheet according to claim 15, characterized in that: The first doping element includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge; and / or The second doping element includes one or more elements selected from the group consisting of B, S, Si and N.
17. The positive electrode sheet according to claim 14, characterized in that: The polyanion positive electrode material includes Li 1+ x Mn 1-y A y P 1-z R z O4, wherein x is any value in the range of -0.100 to 0.100, y is any value in the range of 0.001 to 0.500, z is any value in the range of 0.001 to 0.100, A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ni, Co, Ga, Sn, Sb, Nb and Ge, and R includes one or more elements selected from the group consisting of B, S, Si and N.
18. The positive electrode sheet according to claim 14, characterized in that: The polyanion positive electrode material includes Li h A i Mn 1-j B j P 1-k C k O 4-l D l , wherein A includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W; B includes one or more elements selected from the group consisting of Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge; C includes one or more elements selected from the group consisting of B, S, Si and N; D includes one or more elements selected from the group consisting of S, F, Cl and Br; h is selected from the range of 0.9 to 1.1, i is selected from the range of 0.001 to 0.1, j is selected from the range of 0.001 to 0.5, k is selected from the range of 0.001 to 0.1, l is selected from the range of 0.001 to 0.1, and the polyanion positive electrode material is electrically neutral.
19. The positive electrode sheet according to claim 14, characterized in that: The polyanion positive electrode material also has a coating layer containing carbon.
20. The positive electrode sheet according to claim 19, characterized in that: The carbon-containing coating layer accounts for 1% to 3% by mass in the polyanion positive electrode material.
21. The positive electrode sheet according to claim 14, characterized in that: The ternary system material includes Li a Ni b Co c M1 d M2 e O f R g , where 0.75 ≤ a ≤ 1.2, 0.3 < b < 1.0, 0 < c < 0.4, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 includes one or both elements of Mn or Al, M2 is selected from one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R is selected from one or more elements of N, F, S, Cl.
22. A battery cell, characterized in that: The battery cell comprises the positive electrode sheet according to any one of claims 1 to 21.
23. A battery, characterized in that: The battery comprises the battery cell of claim 22 .
24. An electrical device, characterized in that: The electrical device comprises the battery cell according to claim 22 or the battery according to claim 23.
